1985
DOI: 10.1063/1.448651
|View full text |Cite
|
Sign up to set email alerts
|

Continuous wave optically pumped iodine monofluoride B 3Π(0+) → X 1Σ+ laser

Abstract: A continuous wave optically pumped iodine monofluoride laser operating on the B 311(0+) _ X II + system is described. The laser operated on a series of rovibronic lines originating from v I = 2-5. By tuning the dye laser pump source over a single rovibronic line, spectral structure was produced on the IF laser output that was analyzed and found to be consistent with hyperfine structure in IF. Hyperfine coupling constants were determined in this analysis. Implications for a chemically pumped IF laser are also p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…There has been considerable recent interest in using the interhalogens, 19,20 particularly ClF ͑Refs. 21 and 22͒ and IF, [23][24][25][26][27] for lasers in the visible and UV regions.…”
Section: Introductionmentioning
confidence: 99%
“…There has been considerable recent interest in using the interhalogens, 19,20 particularly ClF ͑Refs. 21 and 22͒ and IF, [23][24][25][26][27] for lasers in the visible and UV regions.…”
Section: Introductionmentioning
confidence: 99%
“…lar IF. Clyne and McDermid 1'2 suggested in 1977 that an electronic transition laser could be made to operate on the B(31"I0+) X(l+) system of IF and Davis et al 3,4 have demonstrated pulsed and CW laser operation on the B -X system using optical pumping of ground state IF produced by the low pressure gas phase reaction of F2 with 12. It has been suggested that it should be possible to construct a true chemical laser in which excited IF(B) is produced directly by a chemical reaction or by other means provided that a sufficiently high concentration of IF(B) (>1 x 10 -3 mbar) can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that it should be possible to construct a true chemical laser in which excited IF(B) is produced directly by a chemical reaction or by other means provided that a sufficiently high concentration of IF(B) (>1 x 10 -3 mbar) can be achieved. 4 Various gas phase chemiluminescent reactions and energy transfer processes involving chemically-produced excited metastable species have been shown to produce IF(B), but as yet none of these schemes has generated a sufficient density of IF(B) to achieve lasing. 5 In this paper, we report the generation of IF(B) by the 248 nm photolysis of a low-pressure gas phase mixture of F2, He and an alkyl iodide (n-C3F7I, C2F5I, CF3I, CH3I, C2H5I or t-C4H9I).…”
Section: Introductionmentioning
confidence: 99%
“…Since then there have been a number of studies of the electronic spectra of this molecule [10][11][12][13][14][15][16]. The ground state rotational spectrum was first observed by Tiemann et al [17] and independently by McGurk and Flygare [18], Recently Nair and Hoeft [19] extended these measurements into the mm-wave region and thus improved the accuracy of the number of the molecular parameters.…”
Section: Introductionmentioning
confidence: 99%